EVALUASI KESESUAIAN LAHAN KECAMATAN KARANGMALANG KABUPATEN SRAGEN JAWA TENGAH UNTUK PENGEMBANGAN TANAMAN PANGAN: - Linda Novita Sari; Susilo Budiyanto; Endang Dwi Purbajanti (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[EVALUATION OF THE SUITABILITY OF LAND FOR THE DEVELOPMENT OF FOOD CROPS IN KARANGMALANG DISTRICT, SRAGEN REGENCY, CENTRAL JAVA]. Evaluation of land suitability was carried out in Karangmalang District to assess land suitability classes for food crops. This research was conducted to determine the limiting factors that result in a decrease in land productivity in the local area. The method used in this research was taking soil samples in 19 land map units based on the results of the base map overlay. Testing of soil samples includes soil texture characteristics, soil pH, organic C, CEC value, Base saturation value, available N content, available P2O5, and available K2O. The matching process is carried out using the SPKL application, then the results of the suitability of the selected land are displayed in map form using the Geographic Information System (GIS). The land suitability class is obtained in the marginal suitability class (S3) with the limiting factors of water availability (wa), oxygen availability (oa), and available nutrients (na). The dominant limiting factor found in all research test areas is rainfall and humidity which are classified as low to high. Improvement efforts that can be made to develop agricultural areas include creating irrigation channels to reduce excess water on the land, creating drainage channels to improve the condition of the drainage system, and applying fertilizer to increase the P2O5 and K2O content in the soil.                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                         ABSTRACT   [EVALUATION OF THE SUITABILITY OF LAND FOR THE DEVELOPMENT OF FOOD CROPS IN KARANGMALANG DISTRICT, SRAGEN DISTRICT, CENTRAL JAVA]. Evaluation of land suitability was carried out in Karangmalang District to assess land suitability classes for food crops. This research was conducted to determine the limiting factors that result in a decrease in land productivity in the local area. The method used in this research was taking soil samples in 19 land map units based on the results of the base map overlay. Testing of soil samples includes soil texture characteristics, soil pH, organic C, CEC value, KB value, available N content, available P2O5, and available K2O. The matching process is carried out using the SPKL application, then the results of the suitability of the selected land are displayed in map form using the Geographic Information System (GIS). The land suitability class is obtained in the marginal suitability class (S3) with the limiting factors of water availability (wa), oxygen availability (oa), and available nutrients (na). The dominant limiting factor found in all research test areas is rainfall and humidity which are classified as low to high. Improvement efforts that can be made to develop agricultural areas include creating irrigation channels to reduce excess water on the land, creating drainage channels to improve the condition of the drainage system, and applying fertilizer to increase the P2O5 and K2O content in the soil. —————————————————–—————————————————————————————— Keyword: food crops, Karangmalang district, land evaluation, land productivity, limiting factors